Colonic Metabolism of Blueberry Polyphenols in Ovariectomized Rats Increases in a Dose-Response Fashion (OR34-06-19). (13th June 2019) - Cladis, Dennis; Debelo, Hawi; Ferruzzi, Mario; Weaver, Connie
Abstract: Objectives: Fruit and vegetable derived polyphenols are often touted for their health benefits and marketed as dietary supplements. Following consumption, polyphenols are extensively metabolized by gut microbiota to small molecular weight phenolics and absorbed in the colon. While these metabolites may drive observed health benefits, the pharmacokinetics of colonic absorption are not well characterized, especially at high dietary supplement doses. To address this, we investigated the dose-response of blueberry polyphenols and colonic metabolites produced over 48 h in a rat model. Methods: Five-month old, ovariectomized, Sprague-Dawley rats were fed a diet containing lyophilized, wild blueberries at 5% (w/w) for one week before being acutely dosed with purified wild blueberry phenolics at four doses (0, 60, 300, or 1100 mg total phenolics/kg bw) and 45 Ca to measure calcium absorption. Blood and urine were collected for 48 h after dosing, with phenolic metabolites extracted, purified, and characterized via UPLC-MS/MS. Results: Total phenolic content of wild blueberries and the purified extract were 3.7% & 27% (w/w), respectively. Among individual phenolics, anthocyanins (1411 & 15, 915 mg/100 g), chlorogenic acid (593 & 1916 mg/100 g), and quercetin species (275 & 2290 mg/100 g) were most prominent. After dosing, phenolic acids, including cinnamic and hippuric acids, were the most prominent microbial metabolites (530–2598 and 271–1263 nmol excreted, respectively); while only smaller amounts of anthocyanins (50–161 nmol excreted) were observed, including unmetabolized anthocyanins in the highest dose group. Most metabolites exhibited maximal blood and urine concentrations within 12 h of dosing, though some (e.g., hippuric acid) peaked up to 24 h after dosing. Finally, calcium absorption was significantly higher in the highest dose group as compared to the control group (p = 0.032). Conclusions: These results indicate that colonic metabolites are absorbed later than their small intestinal counterparts, with variable peak absorption times. The increase in calcium absorption, coupled with the presence of unmetabolized anthocyanins in the highest dose group, suggests that high blueberry polyphenol doses may overwhelm normal metabolic pathways and potentially alter GI function. Funding Sources: NIH.